Sayyadi H. Prenatal Stress+Morphine and Postnatal Re-Exposure to Stress Alter Pentylentetrazol-Induced Epileptic Manifestations in Rats - Nakhjiri, E.; Saboory, E.; Roshan-Milani, Sh.; Rasmi, Y.; Sayyadi, H. (Нейрофизиология, 2016)
We studied effects of restraint-induced stress and morphine co-administration within the prenatal period and of re-exposure to stress at the end of infancy on the body mass and pentylenetetrazol-induced epileptic manifestations in rats. Pregnant rats were divided into six groups (control, restraint-stressed, saline, morphine, stress+saline, and stress+morphine). In the stressed groups, pregnant rats were subjected to restraint stressing twice per day for three consecutive days (starting on pregnancy day 15). Rats in saline and morphine groups received saline and morphine subcutaneously at the same days. In the morphine/saline+stressed groups, rats were exposed to stress and received morphine/saline simultaneously. Control rats were left intact. The pups were weighed at postnatal days (PD) 1, 15, and 22. On P22, half of the pups were re-exposed to stress; then, pentylenetetrazol (PTZ)-induced seizures were recorded. The offspring body mass was significantly smaller in stressed, morphine, and stressed+morphine groups compared to the control. The time to onset of the first tonico-clonic seizure was shorter, while the duration and number of tonico-clonic attacks were greater significantly in the stressed+morphine group compared to other groups. Re-exposure to stress decreased the number of clonic seizures. The number of leg-opening and tail rigidity episodes were smaller in female offspring compared to male ones. Co-administration of restraint stress and morphine within the prenatal period reduces the offspring body mass and increases the seizure vulnerability more severely compared to the respective individual effects In addition, prenatal stress exerts stronger effects on the neural development and epileptic behaviors of the offspring than postnatal stress.